Burmese Grape is an Underexploited Fruit Crop Potential to Use in Phytonutrient Enriched Yogurt Formulation - Sultana, Razia; Shemu, Sanjida; Ali, Aslam; Ahiduzzaman; Rahman, Mostafizar; Rafiquzzaman, S. M.; Haque, M. Amdadul (European Journal of Applied Sciences, 2022)
The present study aimed to investigate the phytonutrients present in Burmese grape (Baccaurea ramiflora) fruit (BGF) followed by an antioxidant-enriched yogurt preparation. The fruit peel was extracted in 100% ethanol, 50% ethanol and water. The total phenolic content (TPC) and total flavonoid content (TFC) were determined as a quantitative measure of phytonutrients. The antioxidant activities both in extracts and yogurt were assessed using ABTS and DPPH radical scavenging assays. The BGF juice contained the highest concentration of TPC (57.25 ± 0.68 µg GA/g) and TFC (73.36 ± 0.75 µg QE/g). The peel extracts exhibited radical scavenging activities according to the order of 100% ethanol > 50% ethanol > water. The yogurt samples containing 0%, 10% and 12% BGF juice secured the overall scores indicating Like moderately to Like very much. Therefore, addition of 12% BGF juice is recommended to formulate a phytonutrient enriched yogurt with acceptable sensory properties.